Basic Radiotherapy Physics and Biology - Chang, David S.; Lasley, Foster D.; Das, Indra J.; Mendonca, Marc S.; Dynlacht, Joseph R. (Springer International Publishing, 2021)
Part I: Radiation Therapy Physics -- Atomic and Nuclear Structure -- Radioactive Decay -- Properties and Production of Radiation -- Interactions of Electromagnetic Radiation with Matter -- Interactions of Particulate Radiation with Matter -- Quantification and Measurement of Dose -- Characteristics of Photon Beams -- Dosimetry of Photon Beams in Water -- Dosimetry of Photon Beams in a Patient -- Dosimetry of Electron Beams -- Physics and Dosimetry of Brachytherapy -- Advanced Treatment Planning for EBRT -- Linac Quality Assurance -- Radiation Protection and Safety -- Quality Management Program -- Special Topics: Hyperthermia and Computers -- MRI linac -- Proton Beam Radiotherapy -- Part II: Radiation Therapy Biology -- Molecular Biology and Signaling -- Cancer Genetic and Molecular Characteristics -- Molecular Mechanisms of DNA Damage and Repair -- Cell Death and Survival Assays -- Fractionated Radiation Survival Models -- Oxygen Effect, Relative Biological Effectiveness and Linear Energy Transfer -- Tumor Micro-environment -- Cell and Tissue Kinetics -- Acute Effects of Total Body Irradiation (TBI) -- Normal Tissue Radiation Responses -- Therapeutic Ratio -- Combined Modality Therapy -- Biology of Brachytherapy, Particle Therapy, and Alternative Radiation Modalities -- Chemomodulation and Immunomodulation of Radiation In Vitro and In Vivo -- Hyperthermia -- Stochastic and deterministic Late Effects -- Radiation Effects in the Embryo and Fetus -- Appendix A: Glossary of Terms and Physical Constants -- Appendix B: List of Radionuclides for Radiotherapy and Imaging